The moral identity profiles of inspiring social studies teachers - EKŞİ, HALİL; KATILMIŞ, AHMET (My University, 2024)
This study aims to explore the moral identity profiles of inspiring social studies teachers. In the research conducted with the systematic grounded theory method, data were collected from 14 teachers using in-depth interviews. These data were analyzed with the technique of continuous comparative analysis. The results show the theoretical items that explain the theory to be gathered around the core category of moral identity and to be constituted of self traits; referenced worldview and beliefs; personality characteristics; ideals, and goals; past experiences; social influences; and educational approach. This study contributes to the explanation of moral identity of inspiring teachers.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; İlköğretim; Sosyal Bilgiler Öğretmenliği; Social Sciences and Humanities; Education; Elementary School Education; Teacher Training in Social Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Social studies; Identity; Moral identity; Inspiring teacher; Grounded theory